Elaboração e avaliação de conteúdo educacional para educação a distância sobre úlceras por pressão - Casaburi, Paula Regina (2009)
In search of qualification, the nursing searches increasingly a continuous update of all the team. One of the strategies that can be used for professional training is the education in service. In this perspective, for the creation of educational projects for training, the nursing has several technological resources in the health institutions and the computer is a facilitator of teaching activities and upgrade. The use of distance education mediated by computer finds wide application in the educational process, providing cost savings and increases the flexibility of teaching. In this context, this project aimed to develop and evaluate an educational content about pressure ulcers to the EAD. For this, placed a survey of the knowledge of a nursing team who worked in an outpatient unit on the prevention and treatment of chronic skin ulcers (pressure ulcers) to support the development of educational content. The development of an educational content about pressure ulcers used the Planning Learning Activities Supported by Computer based on the concepts of the Theory of Meaningful Learning. The course about prevention and treatment of pressure ulcers was created in the virtual learning environment Moodle, using as a structure a division by chapters and consists of an introductory text, introductory exercises, revealing the knowledge (educational content) and the full text. In addition, a glossary, chat, discussion forums, course evaluation, recommended links, notice board and contact have been used as tools. In the final step of this study was made an assessment of educational content for expertises in the nursing subject and distance education. In the assessments were highlighted by all the evaluators the scientific rigor and update of the course available. Also identified some areas for improvement, as increase interactivity with the student and improve the quality of the images presented. This work was possible to verify the importance of information technology for the development of distance education courses for nursing and health education, and the importance of researches about skin ulcers. We identified that the creation of courses with the help of a multidisciplinary team is a strategy that we must use, searching with this the creation of interactive courses with the students, providing greater adherence and understanding of the material provided. We 11 conclude that despite the continued growth of distance education, several investments are still needed to reach the same one of its purposes that is to expand the science education.